2013
DOI: 10.1007/s11418-013-0758-z
|View full text |Cite
|
Sign up to set email alerts
|

The large-leaved Kudingcha (Ilex latifolia Thunb and Ilex kudingcha C.J. Tseng): a traditional Chinese tea with plentiful secondary metabolites and potential biological activities

Abstract: In China, Kudingcha has been used for almost 2,000 years as a tea to quench thirst, remove phlegm, refresh the mind, and improve eyesight. The group of large-leaved Kudingcha is coveted for its potential effects on lipid metabolism, which are attributed to the presence of characteristic ingredients. This contribution reviews studies from the past few decades regarding the plant characteristics, ethnobotanical usages, chemical constituents, and related biological activities of the large-leaved Kudingcha (Ilex l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 30 publications
1
77
0
Order By: Relevance
“…At present, Kudingcha is recorded in the Guangxi Zhuang Nationality Drug Quality Standards. Many studies have indicated that Kudingcha has the effect of reducing lipids [8]. However, due to the bitter taste and low bioavailability for lipid reduction, there are inevitable drawbacks of poor compliance and the need for large doses.…”
Section: Introductionmentioning
confidence: 99%
“…At present, Kudingcha is recorded in the Guangxi Zhuang Nationality Drug Quality Standards. Many studies have indicated that Kudingcha has the effect of reducing lipids [8]. However, due to the bitter taste and low bioavailability for lipid reduction, there are inevitable drawbacks of poor compliance and the need for large doses.…”
Section: Introductionmentioning
confidence: 99%
“…The research proved that the tea could enhance physical fitness to 5 resist the diseases, and is claimed to be good for inflammation (He et al, 2010;Lau et al, 2002). According to historical record, its leaves were used as common part of herbal tea in treating common cold (including flu) and rhinitis, bacterial infection, paralleled with the immune enhancement effects (Li et al, 2013). Besides, In the ancient encyclopedia "Compendium of Materia Medica" written by Li Shizhen in Ming Dynastic (Gao et al, 2006), Ku Ding Cha has also been described as a functional tea, which could alleviate pathogenic wind-heat and promote fluid production to quench thirst (He et al, 2003;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to historical record, its leaves were used as common part of herbal tea in treating common cold (including flu) and rhinitis, bacterial infection, paralleled with the immune enhancement effects (Li et al, 2013). Besides, In the ancient encyclopedia "Compendium of Materia Medica" written by Li Shizhen in Ming Dynastic (Gao et al, 2006), Ku Ding Cha has also been described as a functional tea, which could alleviate pathogenic wind-heat and promote fluid production to quench thirst (He et al, 2003;Li et al, 2013). Apart from Ilex latifolia Thunb, Ligustrum purpurascens Y. C. Yang is also another main original plant of Ku Ding Cha (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tseng, an evergreen arbor, is distributed widely in south region of China. The leaves of this plant have been consumed as a traditional Chinese tea, known as Ku-Ding-Cha (bitter tea) due to its particularly bitter taste, and it has been part of the Chinese diet in Southern China for almost 2000 years (Li et al, 2013;Liu et al, 2009). The medicinal properties of I. kudingcha have been gaining much attention in recent years, including the treatment for cardiovascular and cerebrovascular disease, hyperlipidaemia, the prevention of obesity, anti-diabetic, anti-oxidant, anti-inflammatory, anti-cancer and other bioactive activities (Fan et al, 2012;Liu et al, 2009;Song et al, 2012;Thuong et al, 2009;Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%